IMPACT OF LOAD LAYOUT ON INTERNAL VENTILATION DURING THE TRANSPORT OF BROILERS - Pinheiro,Daniel G. (2022)
ABSTRACT The characterisation of ventilation during the transport of broilers is essential to identify and solve problems related to the microclimate of the load. This study aimed to evaluate the ventilation patterns in alternative load layouts, i.e., with a central span or an air corridor, used in Brazil. Computational fluid dynamics simulations and wind tunnel tests were performed on virtual models and small-scale prototypes, respectively. The results showed that the load layout with a "central span" promoted positive ventilation patterns and increased wind circulation between the crates. However, it reduces the load transport capacity by approximately 20% (70 fewer crates), increasing the number of journeys. Therefore, the modification of the layout can optimise ventilation throughout the load; however, it becomes necessary to reduce the number of crates stacked on the truck, which is not feasible for the commercial transport of broilers because it makes it more onerous.